2021
DOI: 10.51485/ajss.v6i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hot Carrier Impact on Lateral-DMOS with LOCOS feature

Abstract: Hot carrier stress is evaluated on a laterally diffused MOSFET (LDMOS) by TCAD simulation. The device under test is obtained from process simulation under a 1µm CMOS flow available at CDTA. The n-type transistor uses the LOCOS (local oxidation of silicon) and single RESURF (reduced surface field) features. Using the trap degradation model, degradation over time and different biases, the shift of threshold voltage VTH, ON-state resistance RON, saturation current IDsat, and device lifetime are extracted. The shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Next, we examined the transistor gain as a function of frequency for multiple gate voltages, using Mason's unilateral gain (MUG) Figure 5 shows the 2D scalar distribution of the absolute value of the electric field and with its extracted maximum path. The bird's beak and near areas have the highest values, and we reported that it triggers noticeable degradation under hot carrier injection [17,18]. As mentioned earlier, the LDMOS operates in RF modes, thus it is important to determine its frequency response.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Next, we examined the transistor gain as a function of frequency for multiple gate voltages, using Mason's unilateral gain (MUG) Figure 5 shows the 2D scalar distribution of the absolute value of the electric field and with its extracted maximum path. The bird's beak and near areas have the highest values, and we reported that it triggers noticeable degradation under hot carrier injection [17,18]. As mentioned earlier, the LDMOS operates in RF modes, thus it is important to determine its frequency response.…”
Section: Resultsmentioning
confidence: 66%
“…Figure 5 shows the 2D scalar distribution of the absolute value of the electric field and with its extracted maximum path. The bird's beak and near areas have the highest values, and we reported that it triggers noticeable degradation under hot carrier injection [17,18]. Figure 3c shows the output characteristic plotted for various V GS values.…”
Section: Resultsmentioning
confidence: 81%